Carnosic acid inhibits the proliferation and migration capacity of human colorectal cancer cells - Barni, María Verónica (2012)
Colorectal cancer (CRC) is the third most common malignant neoplasm worldwide. The objective of this study was to examine whether carnosic acid (CA), the main antioxidant compound of Rosmarinus officinalis L., would inhibit the cell viability of three CRC cell lines: Caco-2, HT29 and LoVo in a dose-dependent manner, with IC50 values in the range of 24-96 µM. CA induced cell death by apoptosis in Caco-2 line after 24 h of treatment and inhibited cell adhesion and migration, possibly by reducing the activity of secreted proteases such as urokinase plasminogen activator (uPA) and metalloproteinases (MMPs). These effects may be associated through a mechanism involving the inhibition of the COX-2 pathway, because we have determined that CA downregulates the expression of COX-2 in Caco-2 cells at both the mRNA and protein levels. Therefore, CA modulates different targets involved in the development of CRC. These findings indicate that carnosic acid may have anticancer activity and may be useful as a novel chemotherapeutic agent.